Development, Test, and Mechanical Model of the Leak-Proof Magnetorheological Damper - Tu, Jianwei; Li, Zhao; Zhang, Jiarui; Gao, Kui; Liao, Jinpeng; Gao, Jingwei (Frontiers in Materials, 2019)
As a semi-active control device, the magnetorheological (MR) damper has received much concern for its great controllability, quick response and lower input power. However, the problem of liquid leakage is produced after its long-term service, severely affecting its performance and service life. To solve this problem, this paper proposes fully vulcanizing and consolidating viscoelastic material, the cylinder barrel and the piston rod, which replaces the traditional dynamic seal with a static seal and develops a new leak-proof MR damper. Considering that viscoelastic material has certain energy dissipation and fluid-structure interaction with MR fluid, the correction factor of the pressure gradient is introduced to establish the mechanical model of the leak-proof MR damper which is to be tested. The testing result shows that warpage deformation of viscoelastic material weakens the damping force of the MR damper and the weakening effect increases with current intensity. Given the influence of current intensity on the correction factor, the complete mechanical model of the leak-proof MR damper is obtained on the basis of the verified model. Through the comparison between the theoretical calculation curve and the test curve, the revised mechanical model is found to well reflect the mechanical properties of the leak-proof MR damper.